FATHER - AUGUST STRINDBERG (NEW YORK DOVER PUBLICATIONS, 2003)
The Father is often seen as a tragedy in which larger-than-life characters engage in a life-or-death struggle centered on a family conflict. Like a Greek tragedy, The Father has a tight plot structure, a narrow time frame of twenty-four hours, one locale, and a hint of the fatalistic forces at work behind the scenes.
Keywords: Swedish Drama-English Translation